Determinants of Economic Growth in Nusa Tenggara Barat: Analyzing the Impact of Education, Health, Economic and Social Infrastructure, and Employment - Eka Agustiani; Abdul Manan; Endang Astuti; Laila Wardani; Isfiya Febriani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to find empirical evidence of the determinants of education level, health level, economic infrastructure, social infrastructure, and employment on the economic growth rate of West Nusa Tenggara Province (NTB) from 2019 to 2022. Data sources were obtained from secondary data, consisting of macroeconomic variable data for NTB accessed through the BPS website. The data analysis method used was quantitative analysis, employing statistical tests using EViews. The results of the study indicate that education level and employment level have a positive and significant effect on the economic growth of NTB Province, with probabilities of 0.000 (less than 0.05) and 0.0009 (also less than 0.05) for the employment variable. Meanwhile, the health level, economic infrastructure, and social infrastructure have a positive but not significant effect.